The Relationship of Positive Thinking and Forgiving Behavior in Student’s Friendship - Reza Fahmi; Dila Fulnandra; Prima Aswirna (AJIS: Academic Journal of Islamic Studies, 2020)
The objective of this study was to determine the category of positive thinking and forgiving behavior among the students in their friendship. This research applied a quantitative approach where the data were analyzed by using Pearson Correlation analysis. The subjects of this research were 65 students from 78 students in the populations. The data were collected by using the instrument as regards psychological scales, a modification of the Likert scale. It measured the level of positive thinking forgiving behavior. The results of this study revealed that the boarding school's students at Lubuk Lintah have a low level of positive thinking. Furthermore, the students who live in Heler dorm at LubukLintahalso have a low level of forgiving behavior in which the significance value of positive thinking and forgiving behavior was 0,000 with a Pearson Correlation coefficient of 0.666